A Small Macro-Econometric Model - Bidabad, Bijan (American Finance & Banking Review, 2019)
Different sizes of macro-econometric models are used for different policy purposes. In this paper, we introduce a small macro-econometric model that includes macro-aggregates variables that can be solved dynamically and be used as a sample model to be estimated for other countries.